Juror Decision-Making in a Child Trafficking Case: The Impact of Defendant and Victim Gender, Defendant Age, and Defendant Status - Pica, Emily (Journal of interpersonal violence, 2023)
There has been an increase in human trafficking in Canada from 2018 to 2019, which suggests a rising trend in human trafficking, and as such, the number of court cases are likely increasing. Because of this, the current study sought to examine how a defendant and victim’s gender, and defendant social status and age impacted mock jurors’ decision-making in a child trafficking case. Participants (N = 584) read a mock trial transcript depicting a child trafficking case. They were then asked to render a verdict, answer questions relating to perceptions of the victim and defendant and rate their level of agreements on statements concerning sex and human trafficking. Although there was no effect on dichotomous verdict, mock jurors attributed higher guilt ratings to the male trafficker. Moreover, participants reported more favorable perceptions of the victim when the trafficker was female, and the victim was male compared to female. Participants also reported more favorable perceptions of the victim when the trafficker was of high social status and younger compared to older. Additionally, when mock jurors were well-informed about trafficking victim blaming did not occur. The results of the current study provide some insight into juror perceptions of child sex trafficking cases.